Identification and validation of ubiquitination-associated genes of senile osteoporosis based on bioinformatics analysis - Cheng, Xiyue; Liu, Junchuan; Guan, Yiman; Jing, Boya; Zhao, Jing; Cao, Yan (Frontiers in Immunology, 2025)
BackgroundSenile osteoporosis (SOP) is linked to the ubiquitination process, with dysregulation of ubiquitin-mediated protein turnover disrupting bone remodeling and resulting in decreased bone mineral density (BMD). This study aimed to identify biomarkers related to ubiquitination in SOP and explore their molecular regulatory mechanisms.MethodsTranscriptomic data of SOP samples (categorized by high and low BMD) were obtained from public databases. Differential expression analysis, protein-protein interaction networks, and the CytoHubba plugin (using Maximum Neighborhood Component and degree algorithms) were utilized, alongside the Least Absolute Shrinkage and Selection Operator, to identify ubiquitination-related genes (URGs) as potential SOP biomarkers. The diagnostic potential of these biomarkers was assessed through a Support Vector Machine model and a nomogram. Their molecular mechanisms were further investigated using enrichment analysis, immune infiltration analysis, and the construction of regulatory networks. Expression levels of the biomarkers were validated in a SOP rat model, with enzyme-linked immunosorbent assay applied to detect relevant indices.ResultsRPS27A and UBE2E1 were significantly underexpressed in low BMD samples and demonstrated a strong ability to differentiate between patients with varying BMDs, making them potential diagnostic biomarkers for SOP. A positive correlation was observed between RPS27A and UBE2E1 (cor = 0.35, P = 0.026). Both genes were involved in neurodegenerative diseases, critical cellular functions, and key intracellular signaling pathways. Additionally, RPS27A showed a positive correlation with macrophages and monocytes, whereas UBE2E1 exhibited a negative correlation with T follicular helper cells (Tfh) and T helper 17 cells (Th17). The transcription factor MAX and miRNA hsa-miR-106b-5p were identified as potential regulators of both biomarkers. Western blot, immunohistochemistry, and reverse transcription quantitative PCR further confirmed significantly lower expression of RPS27A and UBE2E1 in the SOP group compared to the Sham group.ConclusionThis study successfully identified RPS27A and UBE2E1 as key biomarkers for SOP, demonstrating their diagnostic potential and involvement in important biological pathways and immune responses, thus offering new prospects for therapeutic interventions.